Epistemetrics - Rescher, Nicholas (New York : Cambridge University Press, 2006)
When this book was originally published in 2006, Epistemetrics was not as yet a scholarly discipline. With regard to scientific information there was the discipline of scientometrics, represented by a journal of that very name. Science, however, had a monopoly on knowledge. Although it is one of our most important cognitive resources, it is not our only one. While scientometrics is a centerpiece of epistemetrics, it is not the whole of it. Nicholas Rescher's endeavor to quantify knowledge is not only of interest in itself, but is also instructive in bringing into sharper relief the nature of and the explanatory rationale for the limits that unavoidably confront our efforts to advance the frontiers of knowledge. In particular, his book demonstrates the limitations of human knowledge and will be of great value to scholars working in this area.
Includes bibliographical references (p. 107-110) and index.
Keywords: Epistemetrics; Scientometrics